Special Tables on Scheduled Tribes, Part VIII (II), Vol-III, Series-11 - Banthia, J.K. (Karnataka, 1991)
Mother Tongue for Scheduled Tribes, Mother Tongue, Billingualism and Trilingualism for scheduled Tribes.
Keywords: Tables on Houses and Household Amenities